EFEK INTERAKSI MASA EKUILIBRASI DAN LAJU PENURUNAN SUHU TERHADAP PENINGKATAN KEUTUHAN MEMBRAN PLASMA SPERMA DOMBA PRIANGAN PASCA THAWING (The Interaction Effect of Equilibration Time and Freezing Rate toward the Membran Plasma Sperm Integrity of Priangan Ram Sperm Post thawing) - Ken Ratu Gharizah Alhuur; Soeparna Soeparna; Rd. S. Darodjah (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2020)
In general, the freezing process of semen will have a detrimental effect on the structure and function of spermatozoa. The critical point in the semen freezing process is when the temperature drops to freezing, but this can be overcome by applying the right equilibration period. This study aimed to find out the best the equilibration length, the freezing rate, their interaction in the semen freezing process towards membrane sperm cell integrity of the frozen semen post thawing. This study used Priangan sheep’s semen and was carried out according to a completely randomized design with a 3 x 3 split-plot design arrangement. The main plot was equilibration length, i.e., 0.5, 1.5, and 2.5 hours. The subplot was the freezing rate, i.e., 7.5ºC/mins, 13.5ºC/mins, and 19.5ºC/mins. The result of the study showed that there was a significant interaction (P<0.05) between the equilibration length of 1.5 hours and the freezing rate of 13.5°C/mins on the motility and the membrane sperm cell integrity. In conclusion, the best sperm quality was obtained from the equilibration length of 1.5 hours and the freezing rate of 13.5°C/mins.